2022
DOI: 10.1136/ebmental-2021-300309
|View full text |Cite
|
Sign up to set email alerts
|

Serum folate deficiency and the risks of dementia and all-cause mortality: a national study of old age

Abstract: BackgroundThe association between serum folate deficiency and the risk of dementia in old age is unclear, perhaps owing to small sample sizes, the competing risk of mortality or reverse causation.ObjectiveTo examine the associations between serum folate deficiency and the risks of incident dementia and all-cause mortality in a large national sample of older adults.MethodsA prospective cohort aged 60–75 years (n=27 188) without pre-existing dementia for at least 10 years, was tested for serum concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The role of folic acid in prenatal development has been extensively investigated, having critical roles in neurodevelopment and neuroprotective effects [ 154 ]. Serum folate deficiency was associated with higher risks of dementia and all-cause mortality in the elderly (60–75 years) [ 155 ], but vitamin B9 deficiency is correlated with other metal symptoms, especially depression and cognitive decline in epileptic, neurological, psychiatric, geriatric, and psychogeriatric populations [ 156 ]. Folic acid supplementation (400 μg) significantly improved cognitive function and reduced inflammation responses in elderly subjects with MCI after 12 months of intervention [ 157 ].…”
Section: Pharmacological Interventions To Counteract Oxidative Stress...mentioning
confidence: 99%
“…The role of folic acid in prenatal development has been extensively investigated, having critical roles in neurodevelopment and neuroprotective effects [ 154 ]. Serum folate deficiency was associated with higher risks of dementia and all-cause mortality in the elderly (60–75 years) [ 155 ], but vitamin B9 deficiency is correlated with other metal symptoms, especially depression and cognitive decline in epileptic, neurological, psychiatric, geriatric, and psychogeriatric populations [ 156 ]. Folic acid supplementation (400 μg) significantly improved cognitive function and reduced inflammation responses in elderly subjects with MCI after 12 months of intervention [ 157 ].…”
Section: Pharmacological Interventions To Counteract Oxidative Stress...mentioning
confidence: 99%
“…A recent review of nutritional requirements for adults aged ≥ 65 years proposed that intakes of 400 μg were deemed more appropriate for this age group than the current UK recommendation of 200 μg [ 30 , 34 ]. This is due to the increased risk of deficiency in older people, which is associated with neurological damage and potentially increased risk of dementia [ 35 ]. A secondary analysis of the NDNS data found that ‘health conscious’ egg consumers (consuming > 3 eggs/week and low intake of red or processed meat) had significantly higher intakes of folate than those consuming high amounts of red and processed meats and no eggs [ 36 ].…”
Section: Nutritional Benefits and Risksmentioning
confidence: 99%
“…Folate intake is associated with a reduced risk of AD [ 91 ]. Furthermore, serum folate deficiency is linked to a greater incidence of dementia [ 92 ]. In patients with AD, serum homocysteine (Hcy) levels are substantially higher, and serum folate and vitamin B12 levels are lower than in non-dementia patients [ 93 ].…”
Section: Treatment Of Neurodegenerative Disorders With Epinutraceutic...mentioning
confidence: 99%